ความภักดีต่อผู้ให้บริการโทรศัพท์เคลื่อนที่ของนักศึกษาในสถาบันอุดมศึกษาเขตกรุงเทพมหานคร: Customer Loyalty to Mobile Phone Service Companies among Students in Higher Education Institutions in Bangkok - จักรพันธ์, จักรพันธ์ (Journal of Applied Economics and Management Strategy, 2018)
บทความนี้ มุ่งศึกษาอิทธิพลของคุณสมบัติด้านชีวสังคมของลูกค้า คุณภาพบริการ คุณภาพความสัมพันธ์ และภาพลักษณ์ของผู้ให้บริการที่มีต่อความภักดีต่อผู้ให้บริการโทรศัพท์เคลื่อนที่ของนักศึกษาในสถาบันอุดมศึกษา เขตกรุงเทพมหานครโดยใช้แนวทางการวิจัยเชิงปริมาณเป็นหลัก เก็บรวบรวมข้อมูลด้วยแบบสอบถามจากลูกค้ากลุ่มนักศึกษาระดับปริญญาตรีในสถาบันอุดมศึกษาเขตกรุงเทพมหานคร จำนวน 1,050 ราย และวิเคราะห์ข้อมูลด้วยแบบจำลองโครงสร้าง (SEM) ด้วยโปรแกรมสำเร็จรูป ลิสเรล (LISREL) ผลจากการศึกษา พบว่า ความภักดีต่อผู้ให้บริการโทรศัพท์เคลื่อนที่ของนักศึกษาในสถาบันอุดมศึกษาขึ้นอยู่กับอิทธิพลของภาพลักษณ์ของผู้ให้บริการ คุณภาพความสัมพันธ์ และคุณภาพบริการตามลำดับ โดยตัวแปรดังกล่าวมีอิทธิพลต่อการเปลี่ยนแปลงของความภักดีของลูกค้าในระดับสูง ชี้ให้เห็นว่า ถ้าผู้ให้บริการมีภาพลักษณ์ที่ดี มีสัมพันธภาพที่ดีกับลูกค้า และมีการบริการที่เป็นเลิศแล้ว ลูกค้ากลุ่มนี้จะมีระดับความภักดีเพิ่มขึ้นด้วย จากข้อค้นพบดังกล่าว หากผู้ให้บริการโทรศัพท์เคลื่อนที่ต้องการให้ลูกค้ากลุ่มนักศึกษาในสถาบันอุดมศึกษามีความภักดีต่อผู้ให้บริการมากขึ้น ต้องให้ความสำคัญกับการนำหลักบรรษัทภิบาล และดำเนินธุรกิจด้วยความรับผิดชอบต่อสังคมมาใช้เพื่อสร้างความน่าเชื่อถือ การใช้กลยุทธ์สื่อสารการตลาดเพื่อสร้างอัตลักษณ์ของตราสินค้า สร้างภาพลักษณ์ให้โดดเด่น และเป็นที่ยอมรับในความเป็นผู้นำ ตลอดจนพัฒนาคุณภาพบริการ และรักษาสัมพันธภาพระหว่างกันโดยใช้กลยุทธ์การจัดการความสัมพันธ์กับลูกค้า และประสบการณ์ลูกค้า หากทำได้แล้วจะเป็นส่วนสำคัญในการสร้างความภักดี และการคงอยู่ของลูกค้ากลุ่มนี้กับผู้ให้บริการโทรศัพท์เคลื่อนที่ในระยะยาว The objectives of this research are to study the influence of biosocial aspects of customers, quality of service, quality of relationship and image of mobile phone service providers to the loyalty of students in higher education institutions in Bangkok. Questionnaires were used to collect data from 1,050 students who were undergraduate students in different higher education institutions in Bangkok. The data are analyzed using structural equation modeling (SEM) technique and LISREL software package. The results indicates that the loyalty to mobile phone service companies of students in higher education institutions depends on the mobile service providers’ image, quality of relationship and quality of service, consecutively. These factors have major effect on loyalty in the high-level. The loyalty of students in higher education institutions is positively related to service providers’ image, the relationship with customers and the quality of service. If mobile telephone service providers would like to achieve more loyalty from the students in higher education institutions in Bangkok, they should implement principles of corporate governance and social responsibility to build reliable image and credibility. Moreover, social media could be combined with loyalty program to promote their brands and improve relationship quality with the customers. Besides, additional investment should be considered to enhance sound quality and network coverage. The government should also support more investment to develop the network and enforce the law for equitable services.